Growth of juvenile lodgepole pine in relation to soil and slope - Outslay, Gerald, author; Mogren, Edwin W., advisor; Johnson, Donald D., committee member (Colorado State University. Libraries, 1962)
The thesis is concerned with determining site-tree growth relationships that exist in pure evenage juvenile stands of lodgepole pine. The study is a basis for developing methods that will eventually predict site productivity. A pure evenage stand of lodgepole pine 18 to 20 years in age was chosen for study. Research was limited to an east aspect in this stand. The study area was subdivided into seven positions. Twelve dominant or codominant trees were cut on each position and each tree was subjected to a stem analysis. Three soil pits were dug on each position and soil samples collected from each horizon. A mechanical analysis of the soil was conducted, and soil moisture capacities for each horizon were determined. A total of ten environmental variables were measured and of this number six variables were found to be highly correlated to the tree height. The six variables were slope position, percent exposed rock, potential plant available water in the C horizon, bulk density in the C horizon, average percent silt plus clay in the soil profile, and elevation change per chain. Analysis of variance tests end multiple regressions were applied to the data. Six multiple regressions using tree heights in 1946, 1949, 1952, 1955, 1958, and 1961 as the dependent variables were analyzed. Position of slope was found to be the most critical factor in the study. Differences in tree height were most directly effected by this variable. Evidence obtained from additional statistical analysis and field work indicated that tree height differences at earlier stages in the tree's development are not as strongly dependent upon the six variables. Other variables may be of greater importance. Microclimatic conditions of temperature, humidity, evaporation and rainfall associated with specific slope positions, may influence tree growth In the earlier stages.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Lodgepole pine; Growth (Plants)